Gender and economic growth in Kenya : unleashing the power of women - Ellis, Amanda, 1962- (Directions in development (Washington, D.C.). Private sector development., 2007)
"Kenyan women are making a large - although frequently invisible - contribution to the country's economy, particularly in the agricultural and informal business sectors. But women face more severe legal, regulatory, and administrative barriers to starting and running businesses than do their male counterparts. Gender and Economic Growth in Kenya examines the barriers that are preventing women from contributing fully to the Kenyan economy and makes recommendations for addressing these barriers. Addressing these constraints will not only help women make a full economic contribution, but will also improve their livelihoods and those of their families and help create a more enabling environment for all Kenyan businesses, regardless of the gender of their founders."--Jacket